Land use-induced change in trophic state of Shenzhen Bay (South China) over the past half-century. (August 2019) - Yan, Hongyu; He, Xiufang; Lei, Yuanda; Wang, Yasu; Su, Hong; Jiang, Shijun
Abstract: Mangroves connect terrestrial and marine ecosystems and are sensitive to environmental change, and the sediments within faithfully record long-term changes in the aquatic environment and supplement the generally short monitoring archives. Here we present a sediment-core record of TN, TP, TOC, and C/N ratios from the Futian mangrove wetland, Shenzhen Bay (South China), and compare with our remote sensing-derived land use change and the nearby seawater monitoring records. Our reconstructed record extends the history of tropic state change back to the Year 1958, supplementing the monitoring activity initiated in 1987. More importantly, the results reveal two distinct periods. The pre-1983 period (Year 1958–1982) is characterized by increased nutrient due to agricultural activities, while the post-1983 period (Year 1983–2014) is marked by reduced TP but relatively stable TN values, during which the simultaneous increase in construction lands and C/N ratios suggests enhanced soil erosion due to the rapid urbanization of Shenzhen City. Highlights: Sediment TN and TP measured from a mangrove wetland sediment core Land use change quantified through remote sensing image analysis Historical nutrient variation extended from Year 2014 back to Year 1958 Increasing nutrient levels during pre-1983 period due to agriculture Decreasing TP and stable TN during post-1983 period due to landuse-induced soil erosion from Shenzhen's urbanization